EP1292 Minimally invasive palliative treatment of vulval cancer: is there a role for electrochemotherapy?. (1st November 2019) - Tranoulis, A; Georgiou, D; Mehra, G; Rajkumar, S; Founta, C; Sayasneh, A; Nath, R
Abstract : Introduction/Background: Electrochemotherapy (ECT) represents a locally enhanced chemotherapy that combines the administration of chemotherapeutic agents with cell membrane electroporation via electric pulses. ECT has gained popularity as minimally invasive treatment in vulval cancer. The aim of this meta-analysis was to ascertain the efficacy and safety of ECT amongst vulval cancer patients treated in the context of palliative care. Methodology: A systematic literature review was conducted to identify relevant studies that reported response to ECT amongst women with vulval cancer treated with palliative intent. We performed a single-proportion meta-analysis for the outcomes of overall response, complete response and partial response rate respectively. Sensitivity analysis was performed to address heterogeneity. Results: Four studies were included. The studies were of moderate quality. Pooled results from four studies rendered a summary proportion of 78.81% (95% CI 70.39–86.15) for the outcome of overall response. The pooled proportion for the outcomes of complete and partial response rate was 48.74% (95% CI 30.74–61.49) and 30.18% (95% CI 21.69–39.40) respectively. The outcome of the leave-one-out analysis demonstrated that no single study was found to significantly affect the overall outcome. By omitting one study at a time, overall and complete response ranged from 73.21 to 80.89 and from 45.19% to 53.31% respectively. The follow up ranged from one to 51 months. Significant improvement in quality-of-life was reported. The treatment was generally well-tolerated. The length of stay in the hospital ranged from one to eight days. The safety profile of ECT is favourable. No severe adverse effects were reported. Conclusion: Our study showed that palliative ECT is associated with high response rate, significant improvement in quality-of-life and limited side-effects amongst palliative vulval cancer population. Further studies with longer follow-up and quality-of-life data will be required to further assess its efficacy in this setting. Disclosure: Nothing to disclose